2022
DOI: 10.1101/2022.08.03.22278332
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Combining Sodium MRI, Proton MR Spectroscopic Imaging and Intracerebral EEG in Epilepsy

Abstract: Whole brain ionic and metabolic imaging has potential as a powerful tool for the characterization of brain diseases. In this study we combined sodium MRI (23Na MRI) and 1H-MR Spectroscopic Imaging (1H-MRSI) and compared ionic/metabolic changes probed by this multimodal approach to intracerebral stereotactic-EEG (SEEG) recordings. We applied a multi-echo density adapted 3D projection reconstruction pulse sequence at 7T (23Na MRI) and a 3D echo planar spectroscopic imaging sequence at 3T (1H-MRSI) in 19 patient… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 86 publications
0
4
0
Order By: Relevance
“…Ionic homeostasis is a pre-requisite for proper cellular functioning, with sodium in the nervous system being critical in trans-membrane transport, osmotic and electrostatic regulation and the generation/propagation of action potentials [1][2][3] . As such, the non-invasive, in vivo measurement of sodium concentration by 23 Na-MRI is of interest in the context of neuro-oncological [4][5][6] , neurodegenerative [7][8][9] , demyelinating [10][11][12][13][14][15][16][17][18][19] and cerebrovascular 20 conditions, and in both physiological and pathological neuronal activity [21][22][23][24][25] .…”
mentioning
confidence: 99%
“…Ionic homeostasis is a pre-requisite for proper cellular functioning, with sodium in the nervous system being critical in trans-membrane transport, osmotic and electrostatic regulation and the generation/propagation of action potentials [1][2][3] . As such, the non-invasive, in vivo measurement of sodium concentration by 23 Na-MRI is of interest in the context of neuro-oncological [4][5][6] , neurodegenerative [7][8][9] , demyelinating [10][11][12][13][14][15][16][17][18][19] and cerebrovascular 20 conditions, and in both physiological and pathological neuronal activity [21][22][23][24][25] .…”
mentioning
confidence: 99%
“…In addition, by quantifying the sodium signal fraction with the short T 2 * decay -4- component (f ) this approach may offer a more relevant metric for studying tissue alterations and potentially provide a better link between sodium homeostasis and neuronal excitability in human epilepsy. In a recent study an increase of f in the EZN compared to controls and to PZ and NIZ has been reported, whereas TSC was increased in all regions including PZ and NIZ (Azilinon et al, 2022).…”
Section: (Which Was Not Certified By Peer Review) Preprintmentioning
confidence: 82%
“…Nested Cross-validation Also called double cross validation, this procedure uses two k-fold type loops, meaning that each training fold is also folded. -37- (Azilinon et al, 2022;Grimaldi et al, 2021;Ridley et al, 2017).…”
Section: (Which Was Not Certified By Peer Review) Preprintmentioning
confidence: 99%
“…Ionic homeostasis is a prerequisite for proper cellular functioning, with sodium in the nervous system being critical in trans-membrane transport, osmotic and electrostatic regulation and the generation/propagation of action potentials [1][2][3] . As such, the non-invasive, in vivo measurement of sodium concentration by 23 Na-MRI is of interest in the context of neuro-oncological [4][5][6] , neurodegenerative [7][8][9] , demyelinating [10][11][12][13][14][15][16][17][18][19] and cerebrovascular 20 conditions, and in both physiological and pathological neuronal activity [21][22][23][24][25] .…”
Section: Introductionmentioning
confidence: 99%